Effect of platelet-activating factor on the growth of human erythroid and myeloid CD34+ progenitors - F. Dupuis; N. Gachard; A. Allegraud; C. Dulery; V. Praloran; Y. Denizot (Mediators of Inflammation)
We have assessed the effect of platelet-activating factor (PAF), a biologically active phospholipid present in the human marrow, on the growth of human marrow and blood CD34+ progenitors. While the metabolization rate of PAF by CD34+ cells is low (weak acetylhydrolase and acylation processes) it is readily catabolized by the acetylhydrolase activity present in the growth medium (10% fetal calf serum + 10% 5637-conditioned medium). Treatment of marrow CD34+ cells with the non-metabolizable PAF agonist C-PAF (1 nM to 100 nM) immediately before semi-solid culture significantly (p<0.01) decreased the number of BFU-E but not of CFU-GM colonies. Treatment of marrow or blood CD34+ cells with C-PAF (10-100 nM) for 3 days in liquid medium before semi-solid culture significantly (p<0.01) decreased the number of BFUE and CFU-GM colonies. Treatment of blood CD34+ cells with the two PAF receptor antagonists CV 3988 and BN 52021 (1 μ M) had no significant effect on the number of BFU-E and CFU-GM colonies suggesting no role of endogenous PAF in these processes. These results show that exogenous PAF downregulates human erythropoiesis and myelopoiesis, a result that might be of importance during inflammatory states.